Evaluasi Cold Chain Management Vaksin di Puskesmas Kabupaten Jember - Abdul Syakur; Christyana Sandra; Candra Bumi (Jurnal Manajemen Kesehatan Indonesia, 2021)
Immunization is the most cost-effective health prevention method to suppress the incidence of vaccine-preventable disease. Immunization Program in Jember district is still not optimal with many vaccine-preventable disease cases found. Another problem found in Jember is the management of logistics vaccine that is still not optimal. Based on the activity plan report of ORI Difteri 2018, it is known that the logistics needs of some vaccines do not comply with the allocation received by Jember regency of the province. This condition This was a descriptive study using questionaire and observations data as well as the documentation study of the annual Report of Health Pharmacy Installation (IFK) year 2019. Respondent to this study were immunization officers at primary health care of Jember District. The result of cold chain management evaluation is known that the most are good enaugh. In some primary health care are still hampered insufficient means so that the maintenance of vaccine is still not optimalBased on the result that cold chain management evaluation, the knowledge officer on cold chain management is still lacking good. In the some primary health care, it is known that the equipment canstraints are unavailable. While in the conformity of temperature only one primary helath care is not recommended. And stirage activities are mostly in accordance with SOP.